Technical Perspective Software Is Natural. - Murphy, Gail C. (Communications of the ACM, 2016)
The author offers a technical perspective on the expression of software in natural programming language, with reference to a study on the application of corpus-based methods to understanding software development . He cites possibilities for building tools to help develop software given the treatment of software by statistical approaches built for natural language, as well as the range of potential uses of statistical language models to software.